1999
DOI: 10.1097/00007632-199905150-00018
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Somatosensory Evoked Potential Findings in Acute and Chronic Spinal Canal Compromise

Abstract: Acute, unilateral, unresolved intraoperative SEP deterioration was associated with long-term ipsilateral weakness not predicted by clinical or neurologic findings before surgery. Clinical improvement persisted in 92% of patients, 4% were unchanged, and 4% had persistent neurologic changes during an average 12-month follow-up period. The findings underscore the need for monitoring SEPs during surgery in all patients undergoing invasive lumbar surgery and for rapid identification and intervention should a unilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…Similarly, Robinson, et al, 36 monitored femoral nerve SSEPs in 26 patients undergoing surgery for lumbar fractures and found that five patients had significant intraoperative recording changes, only one of whom had a postoperative deficit. The sensitivity, specificity, PPV, and NPV in this study (100%, 87%, 25%, and 100%, respectively) were similar to those noted by Norcross-Nechay, et al 32 Other supportive series from the scoliosis literature also indicate a significant false-positive rate and rare false-negative reports. 17,36,46 Based on this information, it appears that SSEPs are able to detect many instances of nerve injury during thoracolumbar and lumbar surgery.…”
Section: Somatosensory Evoked Potential Monitoringsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Robinson, et al, 36 monitored femoral nerve SSEPs in 26 patients undergoing surgery for lumbar fractures and found that five patients had significant intraoperative recording changes, only one of whom had a postoperative deficit. The sensitivity, specificity, PPV, and NPV in this study (100%, 87%, 25%, and 100%, respectively) were similar to those noted by Norcross-Nechay, et al 32 Other supportive series from the scoliosis literature also indicate a significant false-positive rate and rare false-negative reports. 17,36,46 Based on this information, it appears that SSEPs are able to detect many instances of nerve injury during thoracolumbar and lumbar surgery.…”
Section: Somatosensory Evoked Potential Monitoringsupporting
confidence: 90%
“…The relevance of these findings to the current discussion is questionable because of disparities between the treatment groups, because the patient population treated was a trauma population, and because the medical and surgical treatment paradigm used in the study is outdated and not currently practiced. Norcross-Nechay, et al, 32 monitored 70 patients they treated with lumbar decompression, instrumentation, and fusion with continuous SSEP monitoring and noted significant changes in 12 cases. In all 12 instances, immediate intraoperative "adjustments" were made and high-dose steroids (1.5 mg/kg dexamethasone intravenously) were given to those patients whose responses did not return to normal.…”
Section: Somatosensory Evoked Potential Monitoringmentioning
confidence: 99%
“…13,14 Unexpectedly, in the current sample, the electromyographic recruitment after surgery was worse than before surgery. Nevertheless, it must be noted that evidence on the natural course of EMG findings in LS patients is not available; therefore, we do not know if the surgery modifies the natural evolution of EMG findings; in other words, we can hypothesize that if the patient did not undergo to surgery, the EMG pattern could be even more involved.…”
Section: Discussionmentioning
confidence: 54%
“…13,14 Unexpectedly, in the current sample, the electromyographic recruitment after surgery was worse than before surgery. 13,14 Unexpectedly, in the current sample, the electromyographic recruitment after surgery was worse than before surgery.…”
Section: Discussionmentioning
confidence: 54%